2021
DOI: 10.1002/ceat.202000442
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Neuro‐Based Computing Paradigm for Simulation of Industrial Olefin Plants

Abstract: A neuro-based computing technique is used for simulation of olefin plants at industrial scale. Artificial neural networks are applied to estimate the flow rate of the main products of the olefin unit from available information in terms of flow rate of feed streams and operating condition of furnaces. The structure of the smart model is determined through a trial-and-error procedure taking the real plant information over four successive years. The proposed paradigm estimates the tonnage of the product streams b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It is possible to place several neurons in some successive layers to create different topologies of the ANN. The MLPNN [ 32 ], CFFNN [ 33 ], RNN [ 34 ], radial basis function neural networks, and general regression neural networks are the most well-known ANN types in this regard. Our literature review confirmed that the first three aforementioned models often provide acceptable accuracy for regression-based problems.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible to place several neurons in some successive layers to create different topologies of the ANN. The MLPNN [ 32 ], CFFNN [ 33 ], RNN [ 34 ], radial basis function neural networks, and general regression neural networks are the most well-known ANN types in this regard. Our literature review confirmed that the first three aforementioned models often provide acceptable accuracy for regression-based problems.…”
Section: Methodsmentioning
confidence: 99%
“…This neuron-based machine learning method is the most widely-used tool as either estimator 65 , 66 or classifier 67 . The working process of the artificial neural network is handled by a combination of linear (LPart) and non-linear (NLPart) operations conducted by the neuron as follows 68 : w , b , and are weight and bias coefficients and activation function, respectively.…”
Section: Estimation Scenarios For Density Of Deep Eutectic Solventsmentioning
confidence: 99%
“…A feedforward MLPNN has three layers of input, interiors, and output 44 46 . MLPNN benefits from a unique training approach known as the backpropagation, and the utilized activation functions in this method are non-linear 47 . The three most common types of activation functions are specified as follows 37 , 48 : …”
Section: Theoretical Backgroundmentioning
confidence: 99%